2018
DOI: 10.12816/0045293
|View full text |Cite
|
Sign up to set email alerts
|

Review on Dental Implantology

Abstract: Aim of the work: in this review, we tried to show all details about dental implant, its components, types in the market, usage, case selection and diagnosis, indications and contraindications. Patients and method: Pubmed, Google Scholar have been used to search for papers that addressed dental implantology, preoperative diagnosis of the cases and both of their medical and dental history were considered during searching. Results: it was obvious that dental implant has been the first choice by patients for repla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…8-14 However, there is limited evidence available with regard to viability and feasibility of digital radiography( vistascan) in dental implantology. 1,2 The present study therefore attempted to explore the idea of possibly using digital radiographs(vistascan) instead of the sophisticated CBCT as a more economic option to assess the implant site and proceed to select the appropriate implant size by comparing the measurements made by both the imaging techniques and analyzing their accuracy. Like the CBCT, vistascan also uses software to make measurements on the radiographic image which enables the clinician to get the required information prior to or during the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8-14 However, there is limited evidence available with regard to viability and feasibility of digital radiography( vistascan) in dental implantology. 1,2 The present study therefore attempted to explore the idea of possibly using digital radiographs(vistascan) instead of the sophisticated CBCT as a more economic option to assess the implant site and proceed to select the appropriate implant size by comparing the measurements made by both the imaging techniques and analyzing their accuracy. Like the CBCT, vistascan also uses software to make measurements on the radiographic image which enables the clinician to get the required information prior to or during the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the need of an accurate diagnostic technique which is also economical, to ensure proper placement of the implants, is the need of the hour. 1 One of the important aspects to be considered during treatment planning of implants is the anatomic landmarks in the area, such as, maxillary sinus posteriorly, the floor of the nose anteriorly in the maxilla and the inferior alveolar nerve in the mandible. The most common cause of complications occurring after implant treatment is due to inaccurate or improper placement of implant, especially violation or lack of consideration of these landmarks.…”
Section: Introductionmentioning
confidence: 99%
“…Then, tin (Sn) is an alloying element that is safe to be made with a Ti alloy. In addition, Sn also could strengthen the alloy Ti (Dos Santos., 2017) so that the Ti-Sn alloy can produce some favourable mechanical properties that can be used as a metal for dental casting 3) .…”
Section: Introductionmentioning
confidence: 99%
“…Due to its high success rate, dental implant is considered as the treatment of choice for missing teeth. [ 1 - 3 ] A systematic review showed that the 5-year survival rate of dental implants in the maxilla was 97.9% and 98.9% in the mandible. [ 4 ] A prospective study stated that within 5 and a ½ years, the survival rate of dental implants was 95.73%.…”
Section: Introductionmentioning
confidence: 99%